ALL THAT IS SOLID MELTS INTO AIR: WANG SHIZHEN, JINPINGMEI, AND THE TAIZHOU SCHOOL. (May 2015) - Hammond, Kenneth J.
Abstract : Wang Shizhen was a key figure in mid-Ming intellectual culture and political life. This essay explores the question of Ming decadence using Wang's writings and his role as a focus of literary and political controversy to highlight the impact of commercialization and materialism on Chinese society and culture.